The Impact of Online Learning Policies on Students' Learning Motivation in the Era of the Covid-19 Pandemic: Dampak Kebijakan Pembelajaran Daring Terhadap Motivasi Belajar Siswa Pada Era Pandemi Covid-19 - Hanifah, Umi; Firdaus, Nida Anisah (Universitas Muhammadiyah Sidoarjo, 2022)
Covid-19 is an epidemic originating from Wuhan, China that spread rapidly throughout the world. Covid-19 spread in Indonesia in early March 2020. The spread of this virus caused losses to many countries in various fields ranging from the economy, tourism, to education. In the field of education, the impact of Covid-19 was forced to make the government change the learning system drastically; all learning activities are carried out online starting from elementary school to college. The purpose of this study is was to describe the impact of online learning policies on the learning motivation of high school students and their equivalents during the Covid-19 pandemic. This study is a qualitative descriptive study. Data collection uses a research questionnaire through a Google form that is distributed to high school students and their equivalents in East Java. Based on the results of the study, respondents revealed more negative impacts than positive impacts. From the results of this research the government is expected to be more mature in determining policies even though it is an emergency policy.